Kopitiam chit chat - Tan, Peggy Pek Tao (Pelanduk Publications (M) Sdn Bhd, 2011)
It is about beliefs, romance, career, and the secret lives of men and women in Malaysia, with hilarious results. It is about East-West cultural collisions and the male-female enigmatic relationships. It is also about how well Malaysians have coped with the diversity around them. This book will touch your life and your bones.